The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.22146/jmh.16728
|View full text |Cite
|
Sign up to set email alerts
|

Model Pemberdayaan Wilayah Pesisir Dalam Menghadapi Pasar Bebas Masyarakat Ekonomi Asean

Abstract: The role of the people are needed to the development, because development success in a country is how the government to make a empowerment community. Local government policy in development has contributed by doing upaya­upaya serious. More indonesia is facing Asean economic community (MEA) in 2016, aimed at as an effort to increase stability the economy in Asean. Continuity of the local government and communities to face the challenges MEA indispensable. Local governments have to make regulatory system warehou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…Namun, di banyak negara, wilayah pedesaan sering menghadapi tantangan yang berbeda dibandingkan dengan daerah perkotaan. Masalah-masalah seperti kesenjangan ekonomi, akses terbatas terhadap layanan dasar, dan infrastruktur yang terbatas seringkali menjadi kendala utama dalam mengatasi kemiskinan dan meningkatkan kualitas hidup di pedesaan (Tinambunan, 2016).…”
Section: Pendahuluanunclassified
“…Namun, di banyak negara, wilayah pedesaan sering menghadapi tantangan yang berbeda dibandingkan dengan daerah perkotaan. Masalah-masalah seperti kesenjangan ekonomi, akses terbatas terhadap layanan dasar, dan infrastruktur yang terbatas seringkali menjadi kendala utama dalam mengatasi kemiskinan dan meningkatkan kualitas hidup di pedesaan (Tinambunan, 2016).…”
Section: Pendahuluanunclassified
“…Several research results showed the importance of empowering coastal areas, which is related to the very importance of the government's attention in making regulations considering the potential of the sea so far has not been maximally utilized. In Hezron Sabar Rotua Tinambunan [1]: Research conducted by Ambariyanto and Denny [2] states that there are four problems faced by coastal areas in Indonesia in general, namely:…”
Section: Introductionmentioning
confidence: 99%
“…Masyarakat pesisir merupakan kelompok masyarakat yang tinggal di wilayah pesisir yang keberadaan ekonominya secara langsung bergantung pada pemanfaatan sumber daya alam yang tersedia di lingkungan pesisir sekitarnya (Tinambunan 2016) Pada dasarnya, banyak orang mengandalkan sumber daya alam di sekitar pantai untuk mencari nafkah. Akibatnya, konsep masyarakat pesisir mendapat perubahan lebih lanjut.…”
unclassified